2013
DOI: 10.1002/pc.22744
|View full text |Cite
|
Sign up to set email alerts
|

High performance polyamide 6 composites prepared by reactive extrusion

Abstract: To improve the properties of polyamide 6 (PA6) composites, a series of modified PA6 composites was prepared by reaction extrusion. An amorphous PA6 was first obtained by the complexing reaction of Li 1 in lithium chloride with amino groups, and then epoxy resins, nano-SiO 2 as well as POE-g-MAH were in turn added into the PA6/LiCl system. The effect of different additives on the crystallization behavior and mechanical properties of PA6 composites was well-studied by X-ray diffraction (XRD), differential scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The mechanism of LiCl as a catalyst is in the form of a complex between it and other reactants, which has been proposed in the literature [7][8][9][10]. In our past work, it was observed that LiCl could react with the amide groups of PA6 by complexing, which changed its crystallization behavior [11]. On the basis of above mentioned knowledge and results, LiCl may promote the acetylation reaction of anhydride groups of PP-g-MAH with amino end groups of PA6 and further the miscibility of PP/PP-g-MAH/ PA6 blends.…”
Section: Introductionmentioning
confidence: 95%
“…The mechanism of LiCl as a catalyst is in the form of a complex between it and other reactants, which has been proposed in the literature [7][8][9][10]. In our past work, it was observed that LiCl could react with the amide groups of PA6 by complexing, which changed its crystallization behavior [11]. On the basis of above mentioned knowledge and results, LiCl may promote the acetylation reaction of anhydride groups of PP-g-MAH with amino end groups of PA6 and further the miscibility of PP/PP-g-MAH/ PA6 blends.…”
Section: Introductionmentioning
confidence: 95%
“…15,16 However, in our previous study, it was observed that LiCl could react with the amide groups of PA6 by complexing, which changed its crystallization behavior and an amorphous PA6 was obtained in the presence of more LiCl. 17 Therefore, based on the above results, LiCl will be added in the process of preparing PP-PA6 composites with excellent properties besides maleic anhydride-grafted polypropylene (PP-g-MAH) as a compatibilizer. It is expected to find out how LiCl will affect the crystallization behavior of PP by its effect on PA6 phase, about which there was no report.…”
Section: Introductionmentioning
confidence: 99%